Interrelation of auto-immune process, endocrine disorders and depression - M. A. Mayorova; N. N. Petrova; U. I. Stroev; L. P. Churilov; Y. Shoenfeld (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Disturbances in immune and endocrine regulation are closely interrelated with development of psychiatric diseases, including affective disorders. Depression may be a characteristic of at least 23 autoimmune diseases. Negative influence on the depression development have: an increased level of proinflammatory cytokines, impairment of T-regulatory cells, kynurenine pathway shift towards production of its potentially neurotoxic metabolites, overproduction of stress hormones, hyperleptinemia, hyperprolactinemia, hypothyroidism, as well as vitamin D, calcidiol and calcitriol deficiency. In this review we analysed the development and accumulation of ideas and facts regarding the interrelation between autoimmune and affective pathology.